Relaciones compliance de la misión institucional y utilización de indicadores de rendimiento no financieros en empresas listadas en B3 - Cunha Callado, Antonio Andre (2021)
This paper aims to investigate the association between the compliance of the institutional mission of open capital Brazilian companies and the use of non-financial performance indicators. To achieve this goal, it was operationalized a descriptive and quantitative research, considering non-financial companies listed on B3. The institutional mission was measured based on the characteristics proposed by Pearce David (1987) and David (1989) studies. Likewise, the indicators of non-financial performance were measured based on the research realized by Marquezan, Diehl and Alberton (2013) and Vargas, Diehl, Ayres, Monteiro (2016). Data referring to nine characteristics associated to mission, as well as non-financial indicators of eight distinct groups were collected in annual reports and institutional websites from the companies by the content analysis. The probabilistic sample consisted in 115 companies referring to the fiscal year of 2018. The significance analysis of the relations was realized using Fisher’s Exact Test. The results found showed evidence concerning the presence of relations between the compliance of the institutional mission and non-financial performance indicators, suggesting that the analyzed companies make use of these indicators to track the compliance of the declarations expressed in the mission. In practical terms, this study contributes by reinforcing the relevance of the institutional mission to the achievement of entrepreneurial objectives and strategies and by demonstrating that the non-financial performance indicators may be preferable in order to monitor whether what was stated in the mission is being achieved. A new perspective on the analysis of non-financial indicators was inserted in the context of researches that analyze the relation between mission and performance, bringing theoretical contributions and providing new insights for discussions related to the topic.